Empowering Persons With Disabilities Through The Creative Economy : An Islamic Economic Perspective In Mallari Village, Awangpone District, Bone Regency. - Sudirman Sudirman; Desy Rahmawati Anwar; Sukardi Sukardi; Muhammad Akbar (STIE Amkop Makassar, 2026)
The main problem in this study is How to Empower People with Disabilities through Creative Economy in the Perspective of Islamic Economics. Furthermore, the main problem is formulated into several sub-problems or research questions, namely First, what is the strategy for empowering people with disabilities through the creative economy in Mallari Village, Awangpone District, Bone Regency? Second, what are the supporting and inhibiting factors in the strategy of empowering people with disabilities through the creative economy in Mallari Village, Awangpone District, Bone Regency? Third, what is the strategy for empowering people with disabilities through the creative economy in the perspective of Islamic economics in Mallari Village, Awangpone District, Bone Regency? In this study, qualitative research was used with a phenomenological approach and a sharia approach. The data sources of this study are primary data: the Mallari Village Government, disabled families and the disabled themselves and secondary data: data obtained through the Qur'an, Hadith, literature, documents, as well as related and relevant archives. Furthermore, the data collection method used is by conducting observations, interviews and documentation. Data analysis in this study is through data reduction, data presentation and conclusion drawing and in this data analysis using SWOT analysis tools. The results of this study show that the strategy of empowering people with disabilities through the creative economy in Mallari Village is in line with the results of the SWOT analysis , namely data collection, village discussions, group meetings, Village MUSRENBANG, mentoring and training on the role of the disabled, and providing space/work opportunities for the disabled. The supporting factors for the disability empowerment strategy through the creative economy of Mallari Village are the existence of mentoring, encouragement in the disabled and their families, the community, and the role of the government. Meanwhile, the inhibiting factors are difficulties in data collection, difficulty accessing transportation/vehicles and lack of accessibility public services. The strategy for empowering people with disabilities through the creative economy is in accordance with the principles of monotheism, the principle of benefit, the principle of responsibility, the principle of free will, and the principle of justice